Prática da leitura na turma do 6° ano do ensino fundamental: em duas escolas da cidade e do campo, respectivamente, no município de Tailândia Pará - FURTADO, Elisama Cordeiro Lima (2024)
This research has a purpose of investigate thepratices in reading school setting so that a reflection of the importance of reading and the ways it made such pratices are implemented in the classroom. As well as seeking to discover if students have the critical sense, and feel entering them in the process of social and academic reading. To obtain these objectives we analyze two schools: A country and urban another, both in the 6th grade of elementary school. The followings issues will be presented: Does the practice of readings being able to promote the inclusion of students in the culture of the readers? After all what is actually being taught as reading at the 6th grade of elementary school? The research used in observation in the classroom and interviews with teachers of a particular grade a series was following in Portuguese Languages classes, living the reality and difficulties presentedin the classroom in elementary school.However it is understood that theReading process is very important to subject, because as he will start reading, it will expand your knowledge and learn how to interpret texts in its different wasy, presenting tools in a pedagogical perspective forming critical citiens engaged to society in which he lives.